2016
DOI: 10.1186/s12914-016-0076-0
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood development in Rwanda: a policy analysis of the human rights legal framework

Abstract: BackgroundEarly childhood development (ECD) is a critical period that continues to impact human health and productivity throughout the lifetime. Failing to provide policies and programs that support optimal developmental attainment when such services are financially and logistically feasible can result in negative population health, education and economic consequences that might otherwise be avoided. Rwanda, with its commitment to rights-based policy and program planning, serves as a case study for examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 12 publications
3
53
0
1
Order By: Relevance
“…Stigma and discrimination are pervasive in many societies. Individuals often report feeling discriminated or stigmatized because of their economic situation, gender or sexual orientation, housing status, social position, ethno-racial status, mental health issues, and substance and alcohol use [1][2][3][4][5][6][7]. Furthermore, individuals with mental disorders face frequent stigma and discrimination even within social services and healthcare settings designed to support them [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Stigma and discrimination are pervasive in many societies. Individuals often report feeling discriminated or stigmatized because of their economic situation, gender or sexual orientation, housing status, social position, ethno-racial status, mental health issues, and substance and alcohol use [1][2][3][4][5][6][7]. Furthermore, individuals with mental disorders face frequent stigma and discrimination even within social services and healthcare settings designed to support them [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [ 84 ] has suggested that healthcare providers’ backgrounds also affect preconceptions. Previous research [ 67 – 69 ] also indicated that gendered responsibilities transform with migration. In the case of the Somali-born mothers, this has not been thoroughly addressed in this paper, which focuses primarily on differences between groups.…”
Section: Discussionmentioning
confidence: 92%
“…Family policies and welfare systems differ between societies and shape the responsibilities of women differently [ 64 – 66 ]. By the same logic, gendered expectations and responsibilities undertaken may transform for an individual as he or she changes social context; for example, through migration [ 67 – 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study showed that CHWs play key roles in linking the country's primary health care system to the community, and mitigating the health professional shortage, by providing basic care. Based on lessons learned in the area of health financing, the government of Rwanda has implemented a community performancebased financing as a response to addressing issues of motivation and retention of CHWs who are organized in cooperatives to ensure accountability and income generation [2,4,8].…”
Section: Community-based Interventions For Maternal Health In Rwandamentioning
confidence: 99%